Idiopathic gingival fibromatosis: A rare case report and review - Yuli Fatzia Ossa; Gus Permana Subita; Harum Sasanti; Nur Rahadiani (Scientific Dental Journal, 2023)
Gingival fibromatosis is an enlargement of the gingiva with firm consistency without bleeding and can affect the maxilla or mandible. Gingival enlargement is caused by many factors, including inflammatory conditions, side effects of systemic drugs, hereditary, or idiopathic. A 7-year-old girl with a chief complaint of gingival enlargement throughout the maxillary and mandible. The condition was noted 3 years ago. This condition was not found in any member of the family, and there was no history of taking any medication. During intraoral examination, a complete enlargement of the maxillary gingiva and mandible was the same around, and bleeding did not exist. The patient was referred for a biopsy, and the histopathology result is consistent with gingival fibromatosis. Gingival enlargement can be caused by many factors; in this case, reported gingival fibromatosis is due to an idiopathic condition.